Life cycle assessment as a tool to promote sustainable thermowood boards: a portuguese case study - Ferreira, J. (2015)
The aim of the present work was to conduct a Life Cycle Assessment study of thermally-modified Atlanticwood® pine boards based on real data provided by the Santos & Santos Madeiras company. Atlanticwood® pine boards have several applications, but are mainly used for exterior decking and the cladding facades of buildings. The LCA study was conducted based on the ISO 14040/44 standard and PCR “Product Category Rules for preparing an environmental product declaration for Construction Products and Construction Services”. Because the precise function of the product or scenarios at the building level is unknown the declared unit is used instead of the functional unit. The declared unit is applicable for an EPD that covers “cradle to gate” and in this case is 1 m3 of Atlanticwood® pine boards. The inventory datasets for the products and processes included in the system boundaries were obtained from the company (specific data). Generic data were obtained and adapted as necessary from the Ecoinvent 3.1 database and from Franklin USA. The inventory analysis and, subsequently, the impact analysis was carried out using the SimaPro8.0.4 LCA software and associated databases and methods. The method chosen for the impact assessment was EPD (2013) V1.01. The results show that more than ¾ of “Acidification”, “Eutrophication”, “Global warming” and “Abiotic depletion” caused by 1 m3 of Atlanticwood® pine boards production is due to energy consumption (electricity + gas + biomass). This was to be expected since the treatment is based on the production of heat and no chemicals are added during the heat treatment process.